2015
DOI: 10.4236/ijcce.2015.42003
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of Natural Gas Production from Unconventional Shale Reservoirs

Abstract: Modeling and simulation of unconventional reservoirs are much more complicated than the conventional reservoir modeling, because of their complex flow characteristics. Mechanisms, which control the flow in the reservoir, are still under the investigation of researchers. However, it is important to investigate applications of mechanisms which are present to our knowledge. This paper presents the theory and applications of flow mechanisms in unconventional reservoir modeling. It is a well-known fact that most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Gas production from shale rocks has gained attention worldwide due to advances in hydraulic fracturing and multi-lateral drilling technologies [1,2]. Shale rocks have affinities for gas storage in the internal surface areas of their pore structures, particularly their organic matter pores, and their natural fractures [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Gas production from shale rocks has gained attention worldwide due to advances in hydraulic fracturing and multi-lateral drilling technologies [1,2]. Shale rocks have affinities for gas storage in the internal surface areas of their pore structures, particularly their organic matter pores, and their natural fractures [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, gas adsorption and desorption mechanisms must be considered during shale gas reserves evaluations and shale gas production predictions respectively [5][6][7]. Research has found that gas production can be significantly under-predicted if "adsorption" is not accounted for in the calculation [1,2,8,9]. The word "adsorption" in this context signals a traditional practice of using adsorption isotherms to obtain desorbed gas volumes during gas production calculations [1,2,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations